Changing incidence of hepatitis B and persistent infection risk in adults: a population-based follow-up study from 2011 in China - Xiaolan Xu; Chensi Wu; Zhuoqi Lou; Chunting Peng; Lushun Jiang; Tianxian Wu; Taiwen Zeng; Yin Dong; Bing Ruan (BMC, 2023)
Abstract Background This study aimed to estimate hepatitis B incidence and chronicity risk in rural adults in China under the background of eliminating viral hepatitis. Methods Hepatitis B surface antigen (HBsAg) screening was conducted every 2 years in demonstration areas since 2011. Individuals with baseline HBsAg-negative were included. Incidence was calculated as the number of HBsAg-positive cases divided by the total person-times. HBsAg-positive individuals were followed up to study the persistent infection (> 6 months), chronic infection (> 12 months), and recovery with hepatitis B surface antibody (anti-HBs). The chi-square test and cox proportional regression analysis were performed. Results There were 8,942 incident cases over 2,138,532 person-years, yielding an average incidence of 0.42 per 100 person-years. HBV incidence decreased rapidly in both genders and all age groups and then kept stable. Male gender, low population density, low gross domestic product per capita, and islanders were associated with higher incidence. Of the positive cases, 4,989 (55.8%) patients were followed up. The persistent infection, chronic infection, and recovery with anti-HBs rates were 32.3%, 31.0%, and 31.4%, respectively. Persistent or chronic infection was more common in younger adults and males, while seroconversion had no concern with gender or age. Conclusions HBV incidence in adult rural residents was decreasing and stayed low. The chronicity rate was relatively high and protective antibodies were induced in only one third. The importance of population-based screening and vaccination for susceptible individuals should be addressed.